Caring for Form: Ali Smith and Contemporary Refugee Life-Writing - Miriam Nandi (Czytanie Literatury)
Refugee life writing draws attention to the actual stories behind the statistics (100 million refugees worldwide, more than 3,000 people drowned while attempting to cross the Mediterranean in 2023 alone) and calls for solidarity across national and ethnic divides. A particularly poignant, but also provocative example of such an act of solidarity is the Refugee Tales project, in which established literary authors collaborate with refugees to relate stories of war, flight, loss, and the brutality of asylum systems in the West. This paper explores the ethical dimensions of telling somebody else’s life zooming in on the example of “The Detainee’s Tale as told to Ali Smith.” Unlike many of the other tales, Smith explains the process of visiting and interviewing two refugees trapped in the British asylum system. While the research on the ethics of Refugee Tales has focused on the questions of “trust” (Rupp) and “precarity” (Sandten) of the refugee condition, this article chooses a different path. It suggests that the ethical questions arising in “As-Told-To Life Writing” (Lindemann) remain in the shadow if seen only in terms of authenticity of voice. Instead of scrutinising the authority of the real-world author, it is worth redirecting the attention to the narrative discourse and the specific forms it takes. Drawing on Caroline Levine’s social formalism, the article investigates the interplay between political and aesthetic forms. In this collision of forms, “The Detainee’s Tale” unmasks and contests the inhumane side of the British asylum system, but it also carefully gestures towards possible ethical alternatives. The ethical aspects of Smith’s contribution are best described in terms of a feminist ethics of care, which values the moral salience of recognising and attending to the vulnerability of others (see Held).